Overview of Preclinical and Clinical Trials of Nanoparticles for the Treatment of Brain Metastases - Muhammad Izhar; Mohamed Al Gharyani; Ahed H. Kattaa; Juan J. Cardona; Ruchit P. Jain; Elaheh Shaghaghian; Yusuke S. Hori; Fred C. Lam; Deyaaldeen Abu Reesh; Sara C. Emrich; Louisa Ustrzynski; Armine Tayag; et al. (Pharmaceutics)
Brain metastases (BM), which most commonly originate from lung, breast, or skin cancers, remain a major clinical challenge, with standard treatments such as stereotactic radiosurgery (SRS), surgical resection, and whole-brain radiation therapy (WBRT). The prognosis for patients with BM remains poor, with a median overall survival (OS) of just 10–16 months. Although recent advances in systemic therapies, including small molecule inhibitors, monoclonal antibodies, chemotherapeutics, and gene therapies, have demonstrated success in other malignancies, their effectiveness in central nervous system (CNS) cancers is significantly limited by poor blood–brain barrier (BBB) permeability and subtherapeutic drug concentrations in the brain. Nanoparticle-based drug delivery systems have emerged as a promising strategy to overcome these limitations by enhancing CNS drug penetration and selectively targeting metastatic brain tumor cells while minimizing off-target effects. This review summarizes recent preclinical and clinical developments in nanoparticle-based therapies for BM. It is evident from these studies that NPs can carry with them a range of therapeutics, including chemotherapy, immunotherapy, small molecule inhibitors, gene therapies, radiosensitizers, and modulators of tumor microenvironment to the BM. Moreover, preclinical studies have shown encouraging efficacy in murine models, highlighting the potential of these platforms to improve therapeutic outcomes. However, clinical translation remains limited, with few ongoing trials. To close this translational gap, future work must address clinical challenges such as trial design, regulatory hurdles, and variability in BBB permeability while developing personalized nanoparticle-based therapies tailored to individual tumor characteristics.